Distillation control, optimization, and tuning fundamentals and strategies - Robbins, Lanny; ProQuest (Firm) (Boca Raton [Fla.] : CRC Press, 2011)
"With a focus on the fundamentals and strategies of distillation columns, this book covers the process variables for continuous distillation columns, as well as four basic control strategies and the typical cases in which they are used. The author defines the inlet and outlet streams and process variables for a distillation column and then explains the overall concept of the separation and purification that is performed. Performance and product quality are described in terms of specification requirements, and tools and techniques for the optimization of quality performance are provided. Figures and graphs are included within the reference to illustrate concepts"--
"This book is written from a perspective that was developed as the result of 37 years of industrial research at The Dow Chemical Company that focused on inventing, developing and implementing industrial separation and purification processes. The work process for research and development is the scientific method as follows: The Scientific Method 1) Define the problem and the opportunity. 2) Search and understand the state-of-the-art. 3) Develop a hypothesis, i.e. a concept or a model. 4) Design and run experiments to test the validity of the hypothesis. 5) Evaluate, summarize and document the results. The main problem in distillation process control is to separate and purify chemical components in liquid and vapor streams while shedding the disturbances that are imposed on the distillation column. The opportunity is to separate the components from a feed stream into new vapor and liquid streams that have increased economic value at a cost that is competitive with other producers. Conducting research in a large corporation provides the opportunity to apply the results of improved performance to many distillation towers in many different businesses"--
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Distillation; Separation (Technology); Electronic books